2009
DOI: 10.1007/s10658-009-9553-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of PCR melting profile for typing of Pseudomonas syringae isolates from stone fruit trees

Abstract: Of thirty fluorescent Pseudomonas isolates originating from symptomatic tissues of sweet (Prunus avium) and sour cherry (Prunus cerasus), plum (Prunus domestica), peach (Prunus persica) and apricot (Prunus armeniaca), 23 were identified as P. syringae using LOPAT tests. Further characterization of those isolates by GATTa and L-lactate utilization tests showed that 10 of them belonged to race 1, six to race 2 of P. syringae pv. morsprunorum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
4
23
0
Order By: Relevance
“…PCR MP, which has not been applied before for bacterial citrus blast and citrus black pit causal agent, allowed the differentiation of the majority of the Pss isolates from citrus and the isolates obtained from other hosts. The results are in agreement with those of the rep‐PCRs used and confirm the recommendation of other authors who recently adopted PCR MP to determine the genetic diversity of other plant‐associated bacteria (Kałużna et al ., ). As confirmed in the present study, these authors stated that PCR MP is a quick, simple, and cost‐effective method for identification and classification of plant pathogens of Pseudomonas .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…PCR MP, which has not been applied before for bacterial citrus blast and citrus black pit causal agent, allowed the differentiation of the majority of the Pss isolates from citrus and the isolates obtained from other hosts. The results are in agreement with those of the rep‐PCRs used and confirm the recommendation of other authors who recently adopted PCR MP to determine the genetic diversity of other plant‐associated bacteria (Kałużna et al ., ). As confirmed in the present study, these authors stated that PCR MP is a quick, simple, and cost‐effective method for identification and classification of plant pathogens of Pseudomonas .…”
Section: Discussionmentioning
confidence: 97%
“…This fingerprinting technique is useful in the study of genetic diversity among P. syringae strains (Louws et al, 1994). The PCR melting profile (PCR MP) method proved to be a useful tool in genetic diversity studies of several bacterial genera, including plant-associated bacteria (Masny & Płucienniczak, 2003;Kału_ zna et al, 2010b). This DNA fingerprinting method allows differentiation of bacteria, even at strain level, based on heterogeneity of their GC content and length of genomic DNA fragments obtained after digestion with endonucleases.…”
Section: Introductionmentioning
confidence: 99%
“…To determine genetic diversity of Xaj isolates, a slightly modified method (Kałużna et al ., ) of PCR MP described by Masny & Płucienniczak () was used. The digestion of 200 ng of DNA with Pst I (Promega) was performed in conditions according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…This DNA fingerprinting method allows differentiation of bacteria, even at strain level, based on heterogeneity of their GC content and length of genomic DNA fragments obtained after digestion with endonucleases (Masny & Płucienniczak, ). Using PCR MP, Pseudomonas syringae isolates were grouped into clusters that strongly corresponded with phenotypically differentiated pathovars and races (Kałużna et al ., ). As this method has not been used for the study of Xaj, its suitability was examined and compared with other commonly used methods.…”
Section: Introductionmentioning
confidence: 97%
“…Hildebrand et al (1982) reported that the general biochemical tests could not separate isolates at the pathovar or intrapathovar level. Kałużna et al (2009) based on repetitive-polymerase chain reaction (REP-PCR) analysis, reported that Pss is a heterogenic pathovar. Civilleri et al (2006) showed that the fAFLP analysis revealed a high genetic heterogeneity in the Pss strains and variability was observed among isolates from the same host plants as well as among isolates within the same antagonistic group or with similar pathogenic activity.…”
Section: Introductionmentioning
confidence: 99%